Efficacy and Safety of Potassium–Titanyl- Phosphate Laser Vaporization for Clinically Non-Muscle Invasive Bladder Cancer - Yang, Dongrong; Xue, Boxin; Zang, Yachen; Liu, Xiaolong; Zhu, Jin; Zhou, Yibin; Shan, Yuxi (Urology Journal, 2014)
Purpose: Although transurethral resection of the bladder tumor (TURBT) is still regarded as thegold standard for the treatment of clinical non-muscle invasive bladder cancer, alternative surgical options remain investigating. Our aim was to evaluate the efficacy and safety of potassium- titanyl-phosphate (KTP) laser for the treatment of primary, clinically non-muscle invasive bladder cancer compared with standard transurethral resection of bladder tumor. Materials and Methods: The data of primary non-muscle invasive bladder cancer patients treated by either KTP laser vaporization (PVB group) or TURBT were analyzed retrospectively. The preoperative conditions and intraoperative complications such as obturator nerve reflex and bladder perforation and postoperative characteristics such as catheterization time and tumor recurrence were compared. Results: The patients' demographics and tumor characteristics in the two groups were comparable. PVB was superior to TURBT in terms of intraoperative complications such as obturator nerve reflex (P = .0289), postoperative bladder irrigation (P = .038) and postoperative catheterization time (P < .0001). Recurrence rate after PVB was also lower than that after TURBT. Conclusion: Our results indicated that PVB is a feasible, safe and effective alternative surgical approach for the management of primary, clinically non-muscle invasive bladder cancer, especially for those with lifetime oral taken anticoagulation medicine, with fewer perioperative complications and lower recurrence.